Prevalence and Economic Burden of Pulmonary Hypertension and Pulmonary Arterial Hypertension Among the Medicaid Population - Marshaleen Henriques King; Chaohua Li; Vincent C. Bond; Dimitri Ford; Peter Baltrus; Harrison W. Farber (Pulmonary Circulation, 2025)
ABSTRACT Pulmonary hypertension (PH) is defined hemodynamically as a mean pulmonary arterial pressure (mPAP) ≥ 20 mmHg, measured at right heart catheterization (RHC). Pulmonary arterial hypertension (PAH) is defined as a mPAP ≥ 20 mmHg with a pulmonary capillary wedge pressure (PCWP) or left ventricular end‐diastolic pressure (LVEDP) of ≤ 15 mmHg and a pulmonary vascular resistance (PVR) > 2 Woods Units (WU). The reported prevalence of PAH in the general population is 0.03–0.05 per 1000 population. However, several studies suggest that the prevalence may be higher among specific sub‐populations. Using Medicaid Analytic Extract (MAX) files, we identified Medicaid beneficiaries who were diagnosed with PH or PAH between 2009 and 2012. The prevalence of PH and PAH was calculated for the overall study population and subgroups based on demographics or co‐morbidities. We used one‐way analysis of variance (ANOVA) tests to compare the differences in hospital bed days and total Medicaid cost across racial subgroups among those with PH and those without PH; Tukey post hoc tests were performed to calculate p‐values for comparing White and Black subpopulations. Prevalence rates ranged between 1.7 and 1.8 per 1000 persons, and the PAH prevalence ranged between 0.4 and 0.5 per 1000 persons for the years reviewed. Significant racial/ethnic disparity in PH and PAH prevalence was observed (p‐value < 0.001), with Black patients having the highest prevalence and Asian patients having the lowest prevalence. Prevalence of PH and PAH were noted to be higher for the Medicaid population than for the general population for all years reviewed. PH and PAH prevalence was noted to be higher among Blacks compared to Non‐Hispanic Whites, while it was significantly lower in Hispanics and Asians. PH/PAH Medicaid patients were noted to account for a greater economic burden compared to the general Medicaid population. Stratifying economic burden by race revealed that American Indian and Alaska Natives with PH had the highest total Medicaid cost for all years reviewed.